EVALUASI PENGGUNAAN SISTEM PERBENDAHARAAN DAN ANGGARAN NEGARATERHADAP PENGELOLAAN DANA ANGGARAN SATUAN KERJA DI WILAYAH KPPN LHOKSEUMAWE - Ramadhani, Desi; Hamdani, Hamdani; Alfianti, Julia (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract— This study aims to determine the Evaluation of the Use of the State Treasury and Budget System on Budget Fund Management at the Lhokseumawe KPPN by looking at the influence of Information Quality. System quality, Service quality, Satisfaction of use, and system use, on Budget fund management at the Lhokseumawe City KPPN. The research method used is a quantitative research method in the form of primary data distributed to 105 respondents consisting of Work Units consisting of 102 Budget Section Work Units (BA) of Ministries/Institutions and 3 Budget Section Work Units (BA) of the State General Treasurer (BUN). The results of the study concluded that Information Quality (X1). System quality (X2), Service quality (X3), Satisfaction of use (X4), and system use (X5), both partially and simultaneously have an effect on Budget fund management at the Lhokseumawe City KPPN (Y) Keywords: Information Quality. System quality, Service quality, Satisfaction of use, and system use, Fund management